2021
DOI: 10.1002/path.5748
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant activation of Rho/ROCK signaling in impaired polarity switching of colorectal micropapillary carcinoma

Abstract: Micropapillary carcinoma (MPC) is a morphologically distinctive form of carcinoma, composed of small nests of cancer cells surrounded by lacunar spaces. Invasive MPC is associated with poor prognosis. The nests of tumor cells in MPC reportedly exhibit reverse polarity, although the molecular mechanisms underlying MPC patterns are poorly understood. Using the cancer tissue‐originated spheroid (CTOS) method, we previously reported polarity switching in colorectal cancer (CRC). When cultured in suspension, the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 45 publications
(73 reference statements)
1
23
0
Order By: Relevance
“…Next, the role of SFK activation was investigated because our previous study revealed that SFK is the key molecule in the polarity switching of colorectal cancer 11,12 . In Ov114 and Ov129 OC organoids 48 hours after embedding in Matrigel, SFK phosphorylation upregulation was induced (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, the role of SFK activation was investigated because our previous study revealed that SFK is the key molecule in the polarity switching of colorectal cancer 11,12 . In Ov114 and Ov129 OC organoids 48 hours after embedding in Matrigel, SFK phosphorylation upregulation was induced (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the polarity status in OC tissues and cell clusters in ascites was evaluated using immunofluorescent imaging. ZO‐1, a tight‐junction protein, and integrin beta 4 (ITGB4) were used as the apical and basal markers, respectively 11,12 . Unsurprisingly, in the OC tissue, ITGB4 was expressed on the membrane facing the stroma in the outermost cells of the cancer cell region (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCR product was cloned into the pENTR4 no ccDB plasmid (Addgene #17424, a gift from Eric Campeau & Paul Kaufman) and transferred into the pLX304 plasmid by the Gateway cloning system. The lentiviral vectors were transfected (Roche, 6366236001; Addgene #12259 and #12260, both gifts from Didier Trono) as previously reported (Onuma et al, 2021). For the pLX304-GFP and -MSI1, blasticidin (2 µg/mL) (Millipore Sigma, 15205) selection was performed.…”
Section: Methodsmentioning
confidence: 99%